Two extended Wells–Dawson arsenomolybdate architectures directed by Na(i) and/or Cu(i) organic complex linkers. Issue 17 (6th April 2017) - Li, Feng-rui; Lv, Jing-hua; Yu, Kai; Zhang, He; Wang, Chun-mei; Wang, Chunxiao; Zhou, Bai-bin
Abstract : Na(i ) and/or Cu(i ) organic complex linkers are introduced into the As2 Mo18 system, leading to two extended hybrid materials, which show highly efficient degradation ability for the refractory dye AP under UV light and electrocatalytic behavior for the oxidation of AA and reduction of NO2 − . Abstract : Two extended Wells–Dawson arsenomolybdates, (imi)2 [{Cu I (imi)2 }2 {Na(imi)2 }{As III As2 V Mo18 O62 }]·2H2 O (1 ) and {Cu I 0.5 (trz)}6 [{Cu I 0.5 (trz)}6 (As2 Mo18 O62 )] (2 ), (imi = iminazole; trz = 1, 2, 3-triazole), are hydrothermally synthesized and extensively characterized. Compounds1 and2 contain a fully oxidized Dawson As2 Mo18 O62 6− (abbreviated as As2 Mo18 ) anion as the parent cluster unit. Compound1 is a symmetric mono-arsenate capped anion cluster modified by two half occupancy AsO3 units, which represents a new capping mode for Dawson clusters. The two adjacent mono-arsenate capped structures are linked by two {Na(imi)2 } bridges to form a dimeric cluster, which, as a tetra-dentate ligand, further connects with adjacent dimers by four {Cu(imi)2 } linkers to form an infinite ladder shaped chain. In compound2, each classical Dawson cluster links six adjacent analogs by six {Cu0.5 (trz)2 } fragments forming an unprecedented 3D network via a unique belt-to-belt staggered pattern. This structure can be simplified as a 2, 6-connected 3-D framework with {8 12 ·12 3 }{8}3 topology. Compounds1 and2 represent the first 1-D and 3-D assemblies of Dawson-type arsenomolybdates, respectively. They display unique electrocatalytic behavior for the oxidation of ascorbic acid (AA) and reduction of NO2 − as well as good photocatalytic properties for the degradation of the difficult-to-degrade dye AP under UV light.